Comparison of the performance of theoretical models of individual and multiproduct inventories in an SME distributor of mass consumer products at the regional level - Garzón Quiroga, Julián (2021)
This article consolidates the simulation results of theoretical models of individual and multiproduct inventory management. Its objective is to compare the cost and service level performance of the models proposed for the most important products of a regional SME marketer of consumer products. The individual inventory management models evaluated were the model (Q, R) for products A and (R, s, S) for products B. In addition, a multiproduct periodic review model per supplier was evaluated. When comparing the results of the evaluated models, it was found that the multi-product periodic review model presented lower costs in six of the eight suppliers evaluated. The result of this work is a source of relevant information to determine the inventory management methodology that the company can implement.